Vicarious trial and error - Redish, A. David (Nat Rev Neurosci, 2016)
When rats come to a decision point, they sometimes pause and look back and forth as if deliberating over the choice; at other times, they proceed as if they have already made their decision. In the 1930s, this pause-and-look behaviour was termed ‘vicarious trial and error’ (VTE), with the implication that the rat was ‘thinking about the future’. The discovery in 2007 that the firing of hippocampal place cells gives rise to alternating representations of each of the potential path options in a serial manner during VTE suggested a possible neural mechanism that could underlie the representations of future outcomes. More-recent experiments examining VTE in rats suggest that there are direct parallels to human processes of deliberative decision making, working memory and mental time travel.